Engineering students learning experience through a unique global project-based learning - Ghazali, Nurzal Effiyana (International Association of Online Engineering, 2021)
Current students must prepare themselves with the necessary skills for employment in the engineering industry. In addition, students should prepare themselves to work globally. Along with the needs, Shibaura Institute of Technology introduces a program named global Project-Based Learning (gPBL). Malaysian students from different educational backgrounds joined this program to experience new skills. The program was participated by 34 students from Malaysia and Japan. Current engineering education is focusing on a course that can foster students' creativity and critical thinking. Therefore, this study explores students' experiences in gPBL and what student skills developed throughout the program. Students reported their experiences through the self-reflective journal. Then, thematic analysis was used to analyze the students' self-reflective journals. The results show gPBL promotes thinking and problemsolving skills, encourages students to work with peers in other fields, and encourages students to adapt to a new culture.